EFL Learners’ Perception Toward MBKM PMM Program - Sartika Sartika; Sam Hermansyah; Buhari Buhari; Syahrir L; Nurul Faradillah (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This study aims to explore the perceptions of English Language Teaching (ELT) students regarding the Independent Campus Learning Program (MBKM) and Independent Student Exchange (PMM) initiatives introduced by the Indonesian government in 2020. The research focuses on a sample of ten fourth-semester students from the English Education Program at Universitas Muhammadiyah Sidenreng Rappang, selected through random sampling techniques. Data was collected using questionnaires and interviews, employing a qualitative methodology for analysis.The findings indicate that the MBKM program is well-facilitated by universities, faculties, and study programs, which has resulted in high student interest and participation. The MBKM initiative allows students to develop diverse skills and knowledge by engaging in learning activities both within and outside their main study programs. It also promotes cultural exchange and integration, as evidenced by the experiences of students participating in the Nusantara module. Overall, the research highlights that the MBKM program significantly enhances students' capacity to become multifaceted individuals, better prepared for the demands of the modern workforce. The program's emphasis on independent and cross-disciplinary learning aligns with the government's objective to create a more versatile and competent graduate pool.